2015
DOI: 10.1103/physrevlett.114.202501
|View full text |Cite
|
Sign up to set email alerts
|

Probing theN=32Shell Closure below the Magic Proton NumberZ=20: Mass Measurements of the Exotic Isotopes<

Abstract: The recently confirmed neutron-shell closure at N=32 has been investigated for the first time below the magic proton number Z=20 with mass measurements of the exotic isotopes (52,53)K, the latter being the shortest-lived nuclide investigated at the online mass spectrometer ISOLTRAP. The resulting two-neutron separation energies reveal a 3 MeV shell gap at N=32, slightly lower than for 52Ca, highlighting the doubly magic nature of this nuclide. Skyrme-Hartree-Fock-Bogoliubov and ab initio Gorkov-Green function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 41 publications
4
93
0
Order By: Relevance
“…Recent mass measurements up to 54 Ca confirmed that result and 'unambiguously establishes a prominent shell closure at neutron number N=32' [83]. Furthermore, mass measurements up to 53 K confirmed the local 'doubly-magic' nature of 52 Ca [84]. However, in the mean square charge radii of the K isotopes, no clear evidence for a subshell closure at N=32 is observed [54].…”
Section: New Methods and Highlights Since 2000mentioning
confidence: 84%
“…Recent mass measurements up to 54 Ca confirmed that result and 'unambiguously establishes a prominent shell closure at neutron number N=32' [83]. Furthermore, mass measurements up to 53 K confirmed the local 'doubly-magic' nature of 52 Ca [84]. However, in the mean square charge radii of the K isotopes, no clear evidence for a subshell closure at N=32 is observed [54].…”
Section: New Methods and Highlights Since 2000mentioning
confidence: 84%
“…[20], may influence their excitation energies and strengths. It has been found recently that the N = 32 subshell closure remains intact below the Ca isotopes [54,55] and theory prognoses a steep increase of 2 + 1 energies in Ne and Mg from N = 28 to N = 32 [20]. Owing to the developments in radioactive isotope beam science, measuring the onset of the expected drop in excitation strength may soon become feasible for magnesium isotopes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that far away from the line of β stability traditional closed-shell numbers may vanish, while others can emerge [1]. For example, neutron shell quenching occurs around N = 20 [2][3][4][5] and N = 28 [6,7], while neutron numbers N = 16 and N = 32 and 34 have been found to feature doubly closed-shell signatures for 24 O and 52,54 Ca [8][9][10][11]. It has been shown that the creation and disappearance of magic numbers are mutually connected [12], raising the question of their respective region of validity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent developments in accelerator technology and isotope separators have made it possible to explore unreached regions of the Segrè chart, yielding many new, exotic phenomena that cannot be explained in the framework of the standard shell model. Several highlights include the weakening of the traditional magic numbers N = 8 [3][4][5], 20 [6], and 28 [7][8][9], while new magic numbers at N = 16 [10,11], 32 [12][13][14][15][16][17][18][19][20], and 34 [21] have been reported. The next conventional neutron magic number, N = 50, has also attracted much attention recently, and investigations into the robustness of this magic number in neutron-rich systems have been encouraged.…”
Section: Introductionmentioning
confidence: 99%